Improving Science Process Skills Through The Socio-Cultural Inquiry Model (Universitas Negeri Semarang, 2019)
This study aims to determine the improvement of science process skills towards grade IV elementary school student science learning using a socio-cultural inquiry model. This research type is Quasy Experimental Design with the form of non-equivalent control group design. The sampling technique used is the type of Cluster Random Sampling. The result of n-gain analysis shows that the Inquiry in the observing, classifying, communicating, and inferring aspect control class gets 0.10; 0.07; 0.09, and -0.08. All aspects of the science process skills are in the low category, while using the socio-cultural Inquiry class observing aspects get 0.61 medium category, classifying get 0.45 as medium category, communicating get 0.26 as low category, and inferring to get 0.30 as low category. The results of the t-test show the difference in the average results of the science process skills on the observing with the result of Sig. (2-tailed) of 0.004 < 0.05 and tvalue of 2.94 > ttable = 2.04. Aspect classifying Sig. (2-tailed) of 0.015 < 0.05 and tvalue of 2.49 > ttable = 2.04. Inferring aspects Sig. (2-tailed) of 0.042 < 0.05 and tvalue of 2.07 > ttable = 2.04. But in the aspect of communicating there is no difference in the average learning outcomes of science process skills between the experimental group and the control group with the results of Sig. (2-tailed) of 0.321 > 0.05 and tvalue 1.000 < ttable = 2.04. The conclusions of this study are the results of the science process skills of the experimental group are higher than the results of the control process of science process skills.